2013
DOI: 10.1007/s12015-013-9431-x
|View full text |Cite
|
Sign up to set email alerts
|

From Bench to Bedside: Review of Gene and Cell-Based Therapies and the Slow Advancement into Phase 3 Clinical Trials, with a Focus on Aastrom’s Ixmyelocel-T

Abstract: There is a large body of preclinical research demonstrating the efficacy of gene and cellular therapy for the potential treatment of severe (limb-threatening) peripheral arterial disease (PAD), including evidence for growth and transcription factors, monocytes, and mesenchymal stem cells. While preclinical research has advanced into early phase clinical trials in patients, few late-phase clinical trials have been conducted. The reasons for the slow progression of these therapies from bench to bedside are as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 92 publications
0
13
0
Order By: Relevance
“…These include bone marrow and peripheral blood mononuclear cells [11][12][13][14][15][16][17], mesenchymal stem cells (MSCs) [18][19][20][21][22], cell lines selected based on the presence of specific markers [15,[23][24][25], adipose tissue-derived cells [26][27][28][29], and induced pluripotent stem cells-derived cells [30,31]. Each of these cell types has shown promise for the treatment of CLI in mechanistic and preclinical studies.…”
Section: Introductionsmentioning
confidence: 99%
“…These include bone marrow and peripheral blood mononuclear cells [11][12][13][14][15][16][17], mesenchymal stem cells (MSCs) [18][19][20][21][22], cell lines selected based on the presence of specific markers [15,[23][24][25], adipose tissue-derived cells [26][27][28][29], and induced pluripotent stem cells-derived cells [30,31]. Each of these cell types has shown promise for the treatment of CLI in mechanistic and preclinical studies.…”
Section: Introductionsmentioning
confidence: 99%
“…Thefirst-in-man clinical trial of therapeutic angiogenesis was conducted using naked plasmid VEGF165 in 1994 [14]. Since then, the proof of concept in preclinical studies has shown promising results, yet few late-phase clinical trials have been performed [15].…”
Section: Gene Therapy For Peripheral Arterial Diseasementioning
confidence: 99%
“…Sources of donor stem cells, autologous versus allogeneic cell sources, types or lineages of cells, remain critically important considerations [43]. It has been noted that public perception of stem cell therapy as well as manufacturing challenges and the regulatory environment all contribute to the small number of late phase (Phase 3) clinical trials undertaken to date and the lack of Food and Drug Administration (FDA) approvals in the US [43]. Nevertheless, there is progress being made and some data with mixed cell populations are interesting.…”
mentioning
confidence: 99%
“…Nevertheless, there is progress being made and some data with mixed cell populations are interesting. For example, Aastrom Biosciences has developed a proprietary cellprocessing technology, ixmyelocel-T, a patient-specific multicellular therapy based on expansion of cells from a small sample of a patient's own bone marrow [43,44]. Ixmyelocel-T uses current good manufacturing practices to expand the MSCs and macrophages.…”
mentioning
confidence: 99%
See 1 more Smart Citation